Analisis Kesesuaian Peralatan Keselamatan pada Kapal Penumpang Cantika Lestari 10C dalam Keadaan Darurat Berdasarkan Ketentuan SOLAS Chapter III/1974 - Titi Vera Tuanaya; Kuncowati Kuncowati; Elva Febriana Anggraeny (Indonesian Maritime Researchers and Lecturers, 2026)
This research is titled “Analysis of Safety Equipment Compliance on Passenger Ship Cantika Lestari 10 C for Emergency Situations Based on SOLAS Chapter III Regulations.” The study aims to assess the compliance of safety equipment on the passenger ship Cantika Lestari 10 C with SOLAS Chapter III regulations; to examine the condition, placement, and maintenance of safety equipment in support of emergency response; and to identify factors influencing this compliance. A qualitative research method was employed, utilizing data collection techniques documentation. such as observation, interviews, and The research results indicate that the majority of safety equipment on the passenger ship Cantika Lestari 10 C complies with SOLAS Chapter III regulations. However, several non-compliances were identified, such as an insufficient number of life jackets to meet the needs of all passengers and crew, the absence of child-specific life jackets, and the lack of certification for SART equipment. Furthermore, the inspection and maintenance of safety equipment were not conducted routinely, tending instead to be prioritized only prior to ship inspections. Interview results also revealed that the contents of the liferaft s require periodic inspection and servicing to ensure completeness and operational readiness.